Determinant Factors Of Nutritional Status In Adolescents - Ramadhani, Firdausi; Adam, Deysi (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2024)
Background: The nutritional status of adolescents in Gorontalo Province is based on data. The prevalence of overweight and obesity in the 13-15 year age group is 16%. The prevalence rate of overweight and obesity in the 16-18 year age group reached 12.4%.            The results of the Gorontalo Province Riskesdas in 2018 showed that physical activity in the low category was high, namely 34.0% and obesity based on BMI in the adult group was 24.4% (Indonesian Ministry of Health, 2018). By knowing the facts above, further research will be carried out regarding the determinants of nutritional status in adolescents in Gorontalo.Purpose: The aim of this research is to determine the determinants of nutritional status in adolescents in Gorontalo City.Methods: The type of research used is Observational Analytical with a Cross sectional approach. The population in this research is teenagers in Gorontalo City. In research, the sampling technique is by accidental sampling. This research will be conducted from January to May 2023. The instrument used in this research is a questionnaire.Conclusion: The results of this research are that there is a relationship between food intake (carbohydrate intake, protein intake and fat intake with the incidence of nutritional status. There is no relationship between stress levels and physical activity and the incidence of nutritional status. Suggestions provide education to teenagers about the importance of nutritional status.Keywords: Determinant factors, nutritional status, adolescents